2021
DOI: 10.1186/s12890-021-01673-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of metagenomic next-generation sequencing in the diagnosis of severe pneumonia caused by Chlamydia psittaci

Abstract: Purpose Psittacosis is a zoonotic infectious disease caused by the transmission of the bacterium Chlamydia psittaci (C. psittaci) from birds to humans. Infections in humans mainly present as community-acquired pneumonia (CAP). However, most cases are treated without diagnostic testing, and the importance of Chlamydia psittaci infection as a cause of CAP is therefore unclear. Diagnostic tools, including culture, serologic test, and PCR-based methods, are available but prone to false negative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Increased pH values and reduced PaCO2 and PaO2 may be associated with fever, increased RR, and severe pneumonia. Increased NE ratio, CRP, ESR, and PCT levels were discovered in most of patients, consistent with the previous study [ 17 , 18 ], suggesting these inflammatory biomarkers may contribute to assessing the infection of C . psittaci .…”
Section: Discussionsupporting
confidence: 91%
“…Increased pH values and reduced PaCO2 and PaO2 may be associated with fever, increased RR, and severe pneumonia. Increased NE ratio, CRP, ESR, and PCT levels were discovered in most of patients, consistent with the previous study [ 17 , 18 ], suggesting these inflammatory biomarkers may contribute to assessing the infection of C . psittaci .…”
Section: Discussionsupporting
confidence: 91%
“…The mortality rate of Chlamydia psittaci infection in foreign countries is less than 1% (Macfarlane JT & Macrae AD., 1983). However, two recent retrospective studies in our country showed that 4 out of 27 patients died due to secondary infection (Yang F, Li J, Qi B & et al, 2021), and 2 out of 13 patients died (Wu HH, Feng LF & Fang SY., 2021). In some other countries, psittacosis is a notifiable disease and must be reported within 48 hours (DE Boeck C, Dehollogne C, Dumont A & et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Wen et al ( 28 ) reported a case of severe C. psittaci pneumonia in which tigecycline was used for treatment, but the treatment effect was not described in detail. Wu et al ( 29 ) reported that three patients received carbapenems, linezolid, or tigecycline in addition to doxycycline treatment after diagnosis, but the outcomes were not stated. Kong et al ( 30 ) reported that two patients with severe C. psittaci pneumonia were not effective in initial treatment with moxifloxacin and were improved after using tigecycline.…”
Section: Discussionmentioning
confidence: 99%